A Normative Study on Human Rights Protection in Armed Conflicts in Papua During the Prabowo Era - Muhammad Rizky Fadhillah (International Journal Labs, 2025)
This study examines the protection of human rights during the armed conflict in Papua during the Prabowo Subianto administration by examining the alignment between security policy and the state's constitutional obligations. The escalation of security operations at the beginning of the new administration has resulted in increasing impacts on civilians, such as displacement, disruption of basic services, and disruption of social stability. This situation raises questions about the extent to which security policy complies with constitutional principles and international humanitarian law, particularly the state's obligation to protect non-derogable rights. This study aims to analyze the normative basis for human rights protection, assess the implementation of security policy, and propose a constitutional alignment mechanism as a model for policy reform in Papua. The method used is normative juridical with a statutory, conceptual, and case-based approach. Primary, secondary, and tertiary legal materials are analyzed qualitatively through systematic interpretation and synchronization of norms. The research findings reveal a significant gap between legal norms and operational implementation, particularly regarding civilian protection, proportionality in the use of force, and accountability for violations. This research offers a novel approach through the constitutional-humanitarian alignment model, a mechanism that integrates constitutional norms and humanitarian law into operational instructions, civilian protection protocols, and a multi-level oversight system. This mechanism is designed to ensure security policies are more aligned with national and international legal standards. The study concludes that constitutional alignment is a strategic step to strengthen state legitimacy, minimize the impact of the conflict on civilians, and increase the effectiveness of handling the armed conflict in Papua.